2018
DOI: 10.1016/j.jhazmat.2018.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of macrolide antibiotics using enriched activated sludge culture: Kinetics, transformation routes and ecotoxicological evaluation

Abstract: The biotransformation of three prominent macrolide antibiotics (azithromycin, clarithromycin and erythromycin) by an activated sludge culture, which was adapted to high concentrations of azithromycin (10 mg/L) was investigated. The study included determination of removal kinetics of the parent compounds, identification of their major biotransformation products (TPs) and assessment of ecotoxicological effects of biotransformation. The chemical analyses were performed by ultra-performance liquid chromatography/q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…The initial activated sludge was unable to degrade macrolide antibiotics at concentration of 1 -10 mg L -1 . After two months of exposure at 10 mg L -1 , the removal efficiency was increased to 99% (Terzic et al, 2018). Accordingly, TrOC-degrading strains have been identified for the removal of previously reported persistent compounds (Moreira et al, 2014;Mulla et al, 2016;Pan et al, 2018;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The initial activated sludge was unable to degrade macrolide antibiotics at concentration of 1 -10 mg L -1 . After two months of exposure at 10 mg L -1 , the removal efficiency was increased to 99% (Terzic et al, 2018). Accordingly, TrOC-degrading strains have been identified for the removal of previously reported persistent compounds (Moreira et al, 2014;Mulla et al, 2016;Pan et al, 2018;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies have demonstrated that long-term exposure of activated sludge microbiome to TrOCs can alter the microbial community and in some cases selectively enrich specific microbes with enhanced affinity for TrOCs biodegradation (Moreira et al, 2014;Navaratna et al, 2012;Qu & Spain, 2010;Terzic et al, 2018;Zhou et al, 2013). An early example was observed for acesulfame (ACE), a synthetic sweetener.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that pure reference standards of these compounds were not available, which prevented obtaining fully quantitative results. Nevertheless, the media from biotransformation experiments described in Terzic et al (2018) 31 were applied as qualitative standards, providing link to structural information, as well as to retention time data for the additional TPs. The overview of the TPs encompassed by this screening is presented in Table 3.…”
Section: Screening For Additional Transformation Productsmentioning
confidence: 99%
“…25 In our earlier study, novel TPs of AZI and roxythromycin (ROX), formed by microbial phosphorylation, were identified in wastewater effluent of a membrane bioreactor, 30 while a recent study on aerobic biodegradation of AZI, CLA and ERY revealed a number of previously unreported, novel TPs and allowed proposing a general transformation pathways scheme for AZI. 31 In addition, non-target analysis of freshwater sediments polluted by pharmaceutical industry effluent indicated the importance of intermediates in AZI synthesis. 32 In order to address the complexity of macrolidederived compounds, we recently developed a novel quantitative analytical method, comprising parent macrolide antibiotics, their major human metabolites and TPs, as well as by-products from AZI synthesis, in wastewater and river water samples.…”
Section: Introductionmentioning
confidence: 99%
“…The cultures AS-1, AS-2 and AS-3 originated from the aeration tank of the Central wastewater treatment plant of the city of Zagreb and were previously enriched on three different amine-moiety containing compounds: azithromycin (10 mg/L), tramadol (20 mg/L) and MTHD (10 mg/L), respectively. The cultures AS-1 and AS-2 were previously proven to be able to degrade macrolide antibiotics (Terzic et al, 2018) and tramadol (unpublished data), respectively. Before being used in M A N U S C R I P T…”
Section: Selection and Preparation Of Microbial Cultures For Preliminmentioning
confidence: 91%